Bacterial profile of urinary tract infections in Diabetic postmenopausal women - Ayoub, Nedhal S.; Abdallah, Khalid; AL-Khazraji, Safyia K. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Urinary tract infection (UTI) is the most common bacterial infection in women in general and in postmenopausal women in particular. Bacteriuria occurs more often in elderly functionally impaired women but in general many of it are asymptomatic.However the risk factors associated with recurrent UTI in elderly women are not widely described.Bacteuria in elderly women is associated with high mortality rates ,however many of thus bacteriuria are asymptomatic (Assel et al.,2009).The belief that diabetes ,a common metabolic disorder is associated with ahigher risk of UTI is widespread,diabetes result in several abnormalities of the host defense system that might result in a higher risk of certain infection. Patient and Method: The prospectiye study included 200 cases of urinary tract infection with diabetes mellitus type 2 in postmenopausal women visiting Medicine out patients and in patients Clinic of Medical City Teaching Hospital in Baghdad city. This study period was from 15 November 2011 till 15 June 2012. Urine Samples were collacted from women under supervision of the specialist’s physicians. General urine examination was accomplished for each patient. For patients suspected with DM type 2the Glycosylated haemoglobin (HbA1c) level was measured considering also the duration of diabetes. The urine samples were inoculated directly onto enrichment and selective media for the isolation of the causative bacteria. The isolates were identified using different microscopical, culture characteristics and biochemical testes. Results: Totally in the four studied groups E.coli was the most common isolates bacteria 39(23.0%),followed by Klebsiella 26(15.3%),Candida albicans 25(14.7%),non hemolytic streptococcus 30(6.5%), Moraxilla catarrhalis 28(16.5%) and diaphtheroid 23(13.6%). Wherease Staphylococcus aureus comprised 13(7.7%). There was no significant relation shipe between type of uropathogenes and HbA1c level .However the relation was significant between uropathogenes and kind of diabetes treatment and duration of diabetes. E.coli and klebsiella growth isolated from diabetic cases was heavy rather than moderate growth. Conclusion: In postmenopausal women the incidence of UTI in age group 50-60 yrs was higher than that of 61-70. However there was no significant difference between diabetic and non diabetic women groups, The risk of UTI was higher with longer duration of diabetes rather than degree of glycemic control (HbA1C), women undergoing pharmacological treatment for diabetes were mainly at higher risk suggesting association between severity of diabetes and risk of UTI, E.coli was the most single isolated organism in all women as well as young women.